Transforming PETE's Initial Standards: Ensuring Social Justice for Black Students in Physical Education. Issue 1 (2nd January 2021) - Blackshear, Tara B.; Culp, Brian
ABSTRACT: Calls to transform the initial Physical Education Teacher Education (PETE) standards to reflect social justice have garnered little attention. Recent events have magnified the racial injustices inflicted upon Black people in America and their ability to participate as full equals in a society influenced and characterized by white supremacy. Using critical race theory (CRT) as a framework, the authors examine the racial formulation of the historical and current installations of SHAPE America's initial PETE standards. Illustrated is the influence of white supremacy in PETE programs, the relationship to physical literacy, and the impact on Black students. After analysis, the authors integrate culturally relevant frameworks, and provide a blueprint of socially just PETE standards that challenge structural racism, and diversity initiatives promoted by SHAPE America and in higher education. The authors conclude that infusing Black perspectives is essential to the advancement of inclusive social justice standards in PETE.